The Effect Of The Performance Of Medan City Cleaning Department Officer On The Satisfaction Of Medan Simpang Limun Market Traders - Nursaimatussaddiya; Cia Cai Cen (Institute of Computer Science (IOCS), 2022)
This study aims to determine whether there is an effect of work quantity and work quality on the satisfaction of Sukaramai traditional market traders at the Medan City Cleaning Service and how big the effect is. The method used in this study is a quantitative method with several tests, namely reliability analysis , classical assumption deviation test and linear regression . Based on the results of the primary data regression which was processed using SPSS 18, the following multiple linear regression equation was obtained: Y = 2.352 + 0.205 X 1 + 0.001 X 2 + 0.598 X 3 . Variables of quantity of work (X1 ) , quality of work (X2 ) and timeliness (X3 ) were able to contribute influence on the variable of merchant satisfaction by 33.3% while the remaining 66.7% was influenced by other variables not examined in the study. These are variables such as service quality and work discipline. From the conclusions above, the authors suggest that the agency should provide more training so that the quantity and quality of employee work increases. Timeliness in cleaning up garbage on the protocol road in the Simpang Limun Medan market area is accelerated so that traders are more flexible and comfortable in selling their products. Employees should work sincerely and provide the best work results in accordance with the targets given by the agency